Need Analysis of the Speaking Syllabus Development for the Eleventh Grade of Vocational School - Ismi Narulita Firda; Albiansyah Albiansyah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The research had the purpose to recognize the pupils’ need in teaching and learning speaking skills to improve speaking syllabus development. The method used qualitative descriptive research. The participants were 60 students of the eleventh grade of vocational high school. The students were divided into two classes of Bina Bangsa Vocational High School. The questionnaire used as an instrument for collecting data. The questionnaire was used for collecting information connected to the target needs and desires. The data were collected in the English Laboratory class. The data collected will be grouped and seen by the majority of students' choices and the least chosen by students. Those data were seen and interpreted the students' needs in learning and mastering speaking skills as guidance for teachers in the future. The results showed that the learners' target of learning speaking is for their higher education and for their future profession. The students prefered practicing speaking skills when learning activities, they desired speaking practice with their friends or pair. They also wanted English speaking to still exist in the curriculum. The learners presumed and wanted the teachers’ role as a facilitator and led them in all English-speaking activities.